2014
DOI: 10.1111/imm.12284
|View full text |Cite
|
Sign up to set email alerts
|

Current approaches to fine mapping of antigen–antibody interactions

Abstract: A number of different methods are commonly used to map the fine details of the interaction between an antigen and an antibody. Undoubtedly the method that is now most commonly used to give details at the level of individual amino acids and atoms is X-ray crystallography. The feasibility of undertaking crystallographic studies has increased over recent years through the introduction of automation, miniaturization and high throughput processes. However, this still requires a high level of sophistication and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 64 publications
(140 reference statements)
0
113
0
Order By: Relevance
“…HX-MS is increasingly being used for the purpose of B cell epitope identification (47,49,50,52,53). The general principles of HX-MS and how the technique relates to other epitope mapping strategies have been covered in several recent reviews (45,54). In a particularly informative study, Malito and colleagues subjected a single MAb directed against factor H binding protein from Neisseria meningitidis to epitope mapping by peptide array, HX-MS, and X-ray crystallography (50).…”
Section: Resultsmentioning
confidence: 99%
“…HX-MS is increasingly being used for the purpose of B cell epitope identification (47,49,50,52,53). The general principles of HX-MS and how the technique relates to other epitope mapping strategies have been covered in several recent reviews (45,54). In a particularly informative study, Malito and colleagues subjected a single MAb directed against factor H binding protein from Neisseria meningitidis to epitope mapping by peptide array, HX-MS, and X-ray crystallography (50).…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical assays, namely, the enzyme-linked immunosorbent assay (ELISA), immunoblotting, and surface plasmon resonance (SPR) analysis, have been used to demonstrate immune response, antigen reactivity, and binding affinity. More recently, structural techniques such as X-ray crystallography and, as described in the studies reported in this issue of Clinical and Vaccine Immunology by Mantis and coworkers, hydrogen-deuterium exchange mass spectrometry (HD-X MS) (1, 2) have been used to resolve antibody and antigen complexes (24). The shift from methods that predominantly identify linear epitopes via denatured antigens or small peptides to native, conformational epitopes limits artifacts that arise in solid-phase binding of antigen, as noted by Mantis and coworkers.…”
Section: T His Commentary Addresses Studies By Mantis and Coworkers mentioning
confidence: 99%
“…Additionally, classification of indirect, structural residues and those involved in direct binding has illuminated interactions involved in neutralization (24). Understanding antibody-antigen contacts at the molecular level will ultimately aid in the engineering of antibodies of higher affinity to their antigens, which has been correlated with neutralization (27,28) On the other hand, crystal structures of antibodyantigen complexes are not always available and can limit the solid-phase binding analysis to a static snapshot of a complex.…”
Section: T His Commentary Addresses Studies By Mantis and Coworkers mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, short CFTR consensus sequences that are homologous to proteins expressed by bacteria or viruses can induce autoimmunity via molecular mimicry [12]. Accordingly, epitope mapping of CFTR is important for understanding autoimmune and immune responses [13], gaining insight into mechanisms of therapeutic antibodies [14,15], and securing and protecting intellectual property [16].…”
Section: Introductionmentioning
confidence: 99%